What users say about technology in mediation: 2020 SIDRA survey, Part 3 - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2020)
In this post on the Kluwer Mediation Blog, the use and appreciation of technology in mediation among client users is analysed.